Preventive Nutrition The Comprehensive Guide for Health Professionals - Bendich, Adrianne; Deckelbaum, Richhard J.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2005)
In this major revision and expansion of a highly respected reference work, the authors have created the most comprehensive and up-to-date review of the nutritional strategies available for the prevention of disease and the promotion of health through nutrition. This new edition combines fully updated versions of the best chapters of the first two editions with updated critical chapters from the much-praised Primary and Secondary Preventive Nutrition, and adds 16 new chapters. Here, practicing health professionals will find all new reviews of lycopene, tomatoes and prostate cancer, soy and cancer prevention; the effects of dietary supplement use on prescription drugs, osteoarthritis, osteoporosis, and cardiovascular disease; balanced, data-driven reviews of the effects of antioxidant supplements on health outcomes, and more. By synthesizing the latest data and integrating it into the broad body of existing information, this book provides in-depth guidance on nutrition and the prevention of cancer, cardiovascular disease, bone diseases, obesity, and diabetes, and on achieving optimal pregnancies and birth outcomes. Of special interest are the new chapters as well as the extensively revised chapters on drug-nutrient interactions, health economics, nutraceuticals, Food and Drug Administration regulations for supplements, carotenoids, the elderly, children, diet and cancer risk, obesity as a chronic disease, diabetes, and immune function. Key point summaries and clinical recommendations are clearly provided at the end of each chapter to highlight critical lessons for the reader. Comprehensive, authoritative, and readily accessible, Preventive Nutrition: The Comprehensive Guide for Health Professionals,Third Edition offers physicians, nutritionists, dentists, pharmacists, dieticians, health educators, policymakers, and research investigators a benchmark integration of the best available data on the role of nutrition in health. Unique in scope, size (over 900 pages), and detail, it demonstrates that many of the major diseases affecting middle-aged adults can be delayed, if not prevented, with simple nutritional approaches.
Preventive Nutrition Overview -- Preventive Nutrition -- Cancer Prevention -- Prevention of Cancers of the Esophagus and Stomach -- Non-Nutritive Components in Foods as Modifiers of the Cancer Process -- Dietary Supplements and Cancer Risk -- Soy Consumption and Cancer Prevention -- Tomato, Lycopene, and Prostate Cancer -- Cardiovascular Disease Prevention -- Iron and Heart Disease -- Homocysteine, Folic Acid, and Cardiovascular Disease Risk -- n-3 Fatty Acids from Fish and Plants -- Antioxidant Vitamin Supplementation and Cardiovascular Disease -- Health Effects of Trans Fatty Acids -- Diabetes and Obesity -- Obesity and Insulin Resistance in Childhood and Adolescence -- Prevention of Pediatric Obesity -- Can Childhood Obesity Be Prevented? -- Obesity and Chronic Disease -- Bone Diseases -- Osteoarthritis -- Calcium Requirements During Treatment of Osteoporosis in Women -- Osteoporosis -- Prevention of Major Disabilities: Improvement In Health Outcomes -- Antioxidant Status and Risk for Cataract -- Antioxidant Nutrients and Prevention of Oxidant-Mediated Diseases -- Nutritional Supplements and Upper Respiratory Tract Illnesses in Young Children in the United States -- Micronutrients and Immunity in Older People -- Vitamin A and the Prevention of Morbidity, Mortality, and Blindness -- Optimal Pregnancy/Infancy Outcomes -- Folic Acid-Containing Multivitamins and Primary Prevention of Birth Defects -- Maternal Nutrition and Preterm Delivery -- Dietary Polyunsaturated Fatty Acids for Optimal Neurodevelopment -- Micronutrient Deficiencies and Maternal Thinness -- Preventive Nutrition: Global Perspectives -- Potential Benefits of Preventive Nutrition Strategies -- Nutrition and Food Policy in Norway -- Prevention of Malnutrition in Chile -- Effect of Westernization of Nutritional Habits on Obesity Prevalence in Latin America -- Effects of Western Diet on Risk Factors of Chronic Diseases in Asia -- Critical Issues for the 21st Century -- Alcohol -- Influence of Medication on Nutritional Status -- Health Claims for Foods and Dietary Supplements -- Teaching Preventive Nutrition in Medical Schools -- Preventive Nutrition Throughout the Life Cycle.
Keywords: Clinical nutrition; Internal medicine; Nutrition .; Clinical Nutrition; Internal Medicine; Nutrition